Corporate communication to promote consumers’ social responsibility? - Fricke, Vera; Schrader, Ulf (Ökologisches Wirtschaften - Fachzeitschrift, 2011)
Companies have discovered Consumers’ Social Responsibility (CnSR). Within CnSR communication consumers are addressed upon their individual responsibility for a behavioural change towards sustainability. Can CnSR communication strengthen sustainable consumption in the mainstream or is it mere greenwashing?